SWOT Analysis and QSPM for Digitalization of PT Mandiri Tunas Finance - Puji Biso Santoso; Meilita Tryana Sembiring; Sugih Arto Pujangkoro (GoAcademica Research & Publishing, 2023)
With the development of businesses that maximize technology, economic development in several parts of the world is very rapid. Competition occurs a lot in various kinds of daily needs, including competition in the business world to achieve consumer satisfaction. But on the other hand, there are sections of society that have not been able to buy the goods they need with the resources that these individuals have. Where this encourages the emergence of finance companies that help people to be able to buy goods they need by using resources from finance companies. Based on the results of this research, even though PT. MTF can dominate the other 7 leasing companies in terms of